PID Control Perspective: Techniques and Uses - Wisam Subhi Al-Dayyeni; Hussam Saleh Mahmood (Edison Journal for Electrical and Electronics Engineering)
This article covers both conventional and modern methods for PID tuning and its appli-cations in an array of fields. Because of its simple layout, ease of use, and ongoing research into PID tuning, PID control is used in the vast majority of control systems that are now in use. The following is the order of the tackles addressed in the paper: PID tuning occurs utilizing optimization rules that range from traditional to modern. In an age of control systems and biomedical applications, this work aims to examine the literature on PID control. A study of the evolution of conventional PID and its integration with intelligent control has been executed, taking into account a number of ap-plication fields. This document's main goal is to provide readers with an in-depth understanding of PID commands in many application areas.